The Problem of Uncertified Waqf Land in Gorontalo City - Muh Rezqy Musa (Estudiante Law Journal, 2026)
This research aims to determine the factors that cause waqf land to be uncertified in Gorontalo City. The research method used is empirical with a qualitative approach and then the data will be analyzed descriptively. The results of this research show that the factors inhibiting the protection of uncertified waqf land rights are: first, lack of public understanding and awareness which results in waqf land being given without going through proper legal procedures, such as obtaining certificates and official registration. Second, the complexity of administrative and legalization procedures resulting from complicated bureaucracy and lack of technical support from the government are additional factors that make it difficult to process waqf land certificates. Convoluted processes and lack of access to technical assistance mean that Nazirs often have difficulty understanding the necessary administrative requirements. Third, the limited protection of waqf land rights means that waqf land often remains uncertified and not managed well, causing the potential social and religious benefits of waqf to not be felt optimally by the community.